ЗБЕРЕЖЕНІСТЬ БАКТЕРІЙ РОДУ AZOTOBACTER НА НАСІННІ CUCUMIS SATIVUS L. ЗА ДІЇ РІЗНИХ ТЕМПЕРАТУР - Білоконська, О. М.; Козар, С. Ф.; Євтушенко, Т. А.; Усманова, Т. О. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2018)
The results of studies on the effect of temperature on the preservation of Azotobacter chroococcumM-70 and Azotobacter vinelandii M-X cells on the seeds of Cucumis sativus L. are presented. In threemonths, the number of bacterial cells on the seeds, which were kept at + 4°C, was significantly higherthan the parameters of the storage of seeds at +28° С. Azotobacter cysts were preserved better thanvegetative cells. To increase the viability of bacterial cells on the seeds, it is proposed to use a complex ofchemical substances that provides better survival of both vegetative cells and Azotobacter cysts. Theresults of the studies can be used to develop new ways to improve the viability of useful soilmicroorganisms on seeds of agricultural crops